Aerated drinks increase gastric volume and reduce appetite as assessed by MRI: a randomized, balanced, crossover trial. Issue 2 (3rd December 2014) - Murray, Kathryn; Placidi, Elisa; Schuring, Ewoud AH; Hoad, Caroline L; Koppenol, Wieneke; Arnaudov, Luben N; Blom, Wendy AM; Pritchard, Susan E; Stoyanov, Simeon D; Gowland, Penny A; Spiller, Robin C; Peters, Harry PF; et al.
ABSTRACT: Background: Compared with nonaerated, isocaloric controls, aerated foods can reduce appetite throughout an entire dieting day. Increased gastric volumes and delayed emptying are possible but unexplored mechanisms. Objective: We tested the hypothesis that aerated drinks (foams) of differing gastric stability would increase gastric distension and reduce appetite compared with a control drink. Design: In a randomized, balanced, crossover trial, 18 healthy male participants consumed the following 3 skimmed-milk–based test products (all 110 kcal): 2 drinks aerated to foams by whipping (to 490 mL), one drink that was stable in the stomach [stable foam (SF)], and one drink that was less stable in the stomach [less-stable foam (LSF)], and a nonaerated drink [liquid control (LC); 140 mL]. Over 4 h, stomach contents (foam, air, and liquid) were imaged using magnetic resonance imaging (MRI), and self-reported appetite ratings were collected and quantified by the area under the curve or time to return to baseline (TTRTB). Results: Compared with the LC, both foams caused significantly increased gastric volumes and reduced hunger (all P < 0.001). Compared with the LSF, SF further produced a significantly slower decrease in the total gastric content ( P < 0.05) and foam volume ( P < 0.0001) and a longer TTRTB (197 compared with 248 min, respectively; P < 0.05), although the hunger AUC was not statistically different. Results for other appetite scales were similar. Conclusions: With this MRI trial, we provide novel insights on the gastrointestinal behavior of aerated drinks by measuring separate volumes of foam, liquid, and air layers in the stomach. Appetite suppression induced by foams could largely be explained by effects on gastric volumes and emptying, which may be further enhanced by foam stability. This trial was registered at clinicaltrials.gov as NCT01690182.